Literasi Gizi dan Konsumsi Gula, Garam, Lemak pada Remaja di Kota Padang - Erina Masri; Novida Shella Nasution; Risya Ahriyasna (Jurnal Kesehatan, 2022)
The Individual Food Consumption Survey Analysis show that 3 out of 10 people in Indonesia (29.7%) consume sugar, salt, and fat exceeding the recommendations. The impact in adolescents is obesity and impaired nutritional status. The level of nutritional literacy has a close relationship with adolescent eating intake. This research was aimed to analized the relationship of nutritional literacy with the consumption of sugar, salt, and fat in junior high school students in Koto Tangah District of Padang City. This research was an observational analytic with a cross sectional design.  The sample of this research was 92 junior high school students in Padang, by used purposive sampling techniques. The research was carried out from January to May 2021. Research variables consist of nutritional literacy,consumption of sugar, salt and fat. Nutritional literacy levels were measured using the Newest Vital Sign questionnaire and sugar salt  fat consumption using the Semi Quantitative Food Frequency. The statistical test used is the chi-square test. The results was there is a relationship between nutritional literacy and sugar consumption (p = 0,000<0.05), a relationship between nutritional literacy and salt consumption (p = 0,000<0.05), and a relationship between nutritional literacy and fat consumption (p = 0,002<0.05). It can be concluded that nutritional literacy has a meaningful relationship with the consumption of sugar, salt, and fat. Responding to this, the school should conduct counseling with materials on nutritional literacy, recommendations for sugar, salt, and fat consumption, and the impact of consuming sugar, salt, and fat, excessively on the health and achievement of students in school.